2018
DOI: 10.1039/c7an02022h
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive and prospective diagnosis of coronary heart disease with urine using surface-enhanced Raman spectroscopy

Abstract: A prospective diagnosis method for coronary heart disease (CHD) using human urine based on surface-enhanced Raman spectroscopy (SERS) is proposed, and could provide valuable information for judging whether to perform percutaneous coronary intervention (PCI) in clinics. Here, urine samples from 87 patients with CHD, including patients with PCI before operation (degree of cardiovascular congestion above 70%) and without PCI (degree of cardiovascular congestion under 70%), and 20 healthy humans were measured usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 18 publications
0
14
1
2
Order By: Relevance
“…С чрезмерной экспрессией гена PDGF связывают развитие многих ССЗ, таких как атеросклероз, аневризма аорты и ИБС [23]. Молекула PDGF существует в виде нескольких димеров, ранее было выявлено, что димер PDGF-BB может быть использован в качестве биомаркера для диагностики ИБС [24]. Был (2018) использован метод КР-спектроскопии для сравнения образцов мочи пациентов с ИБС с образцами мочи здоровых добровольцев [24].…”
Section: идентификация биомаркеров ссз C помощью спектроскопии крunclassified
See 1 more Smart Citation
“…С чрезмерной экспрессией гена PDGF связывают развитие многих ССЗ, таких как атеросклероз, аневризма аорты и ИБС [23]. Молекула PDGF существует в виде нескольких димеров, ранее было выявлено, что димер PDGF-BB может быть использован в качестве биомаркера для диагностики ИБС [24]. Был (2018) использован метод КР-спектроскопии для сравнения образцов мочи пациентов с ИБС с образцами мочи здоровых добровольцев [24].…”
Section: идентификация биомаркеров ссз C помощью спектроскопии крunclassified
“…Молекула PDGF существует в виде нескольких димеров, ранее было выявлено, что димер PDGF-BB может быть использован в качестве биомаркера для диагностики ИБС [24]. Был (2018) использован метод КР-спектроскопии для сравнения образцов мочи пациентов с ИБС с образцами мочи здоровых добровольцев [24]. Авторам удалось идентифицировать в моче у ряда пациентов с ИБС характерный пик (1509 см -1 ), соответствующий присутствию PDGF-BB.…”
Section: идентификация биомаркеров ссз C помощью спектроскопии крunclassified
“…Platelet-derived growth factor (PDGF) is a mitotic factor that contributes to the development of atherosclerosis and coronary heart disease (CHD) and exists as a series of dimers, of which the PDGF-BB dimer has been demonstrated to act as a biomarker for CHD [ 80 ]. Using Ag colloids and urine samples from 87 CHD patients both with and without percutaneous coronary intervention (PCI) and 20 healthy human urine samples, Yang et al were able to directly identify a characteristic peak (1509 cm −1 ) corresponding to the presence of PDGF-BB, and using PCA-LDA, constructed a model for diagnosis that had 87.9% sensitivity and 87.0% specificity using the PDGF-BB peak, showing the great potential of SERS as a diagnostic clinical technique for CHD.…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…In view of these advantages, the label-free SERS approach has taken a central seat in screening and predicting the risk of human diseases, such as human cancers Wang et al, 17 infectious disease, 18 and cardiovascular disease. 19 In this study, AuNPs are used as the enhanced substrate to magnify the Raman signals of living cells largely because of their high sensitivity, good biocompatibility, and ease of use. It has been reported that different sizes and concentrations of AuNPs can cause some degree of toxic effects in living cells.…”
Section: Introductionmentioning
confidence: 99%